Cost Analysis of Single-Dose Hepatitis B Revaccination Among Infants Born to Hepatitis B Surface Antigen-Positive Mothers and Not Responding to the Initial Vaccine Series. (May 2018) - Hall, Eric W.; Rosenberg, Eli S.; Trigg, Monica; Nelson, Noele; Schillie, Sarah
Objectives: Infants born to mothers who are hepatitis B surface antigen (HBsAg) positive are at risk for perinatal hepatitis B infection. As prevention, these infants receive a series of 3 or 4 doses of hepatitis B vaccine starting at birth and postvaccination serologic testing. Infants with antibody levels <10 mIU/mL are considered vaccine nonresponders and should be revaccinated. The objective of this cost analysis was to assess a single-dose revaccination strategy among infant nonresponders. Methods: We used a decision analytic tree to compare the costs of a single-dose revaccination strategy with the costs of a 3-dose revaccination strategy. The analysis consisted of 3 epidemiologic scenarios that varied levels of previous protection among infants indicated for revaccination. We assumed health outcomes in each strategy were the same, and we evaluated costs from the societal perspective using 2016 US dollars. We conducted sensitivity analyses on key variables, including the minimum required efficacy of a single revaccination dose. Results: In all analyses, the single-dose revaccination strategy was a lower-cost option than the 3-dose revaccination strategy. Under the assumption that all revaccination visits were previously unscheduled, single-dose revaccination reduced the cost per infant by 119.81 to 155.72 (depending on the scenario). Across all scenarios, the most conservative estimate for the threshold efficacy (the minimum efficacy required to result in a lower-cost option) value of single-dose revaccination was 67%. Conclusions: For infants who were born to HBsAg-positive mothers and who were not responding to the initial vaccine series, a single-dose revaccination strategy, compared with a 3-dose revaccination strategy, reduced costs across several scenarios. These results helped inform the Advisory Committee on Immunization Practices' vote in February 2017 to recommend single-dose revaccination.